Desquamated Epithelial Cells of Unstimulated Human Whole Saliva Express Both EGF Transcript and Protein - Alexandra Aidoukovitch; Sara Bodahl; Ellen Tufvesson; Bengt-Olof Nilsson (Hindawi Limited, 2022)
Objective. The aim of this study was to investigate if desquamated oral epithelial cells (DOECs) express the epidermal growth factor (EGF) and if these cells thereby may contribute to salivary EGF contents. Background. DOECs have recently been shown to harbor the antimicrobial peptide LL-37, proposing that they may also store other biologically important salivary peptides/proteins. The EGF peptide is a growth factor which plays a critical role to maintain epithelial integrity and promote epithelial healing. The EGF is produced by salivary glands, but it is not known whether DOECs contain the EGF and thereby contribute to salivary EGF levels. Materials and Methods. DOECs were isolated from unstimulated whole saliva collected from four healthy volunteers. EGF protein expression was determined in cell lysates by dot blot and ELISA. Cellular distribution of cytokeratin, the proliferation marker Ki67, and EGF immunoreactivity were assessed by immunocytochemistry. EGF gene expression was investigated by qPCR. Expression of EGF transcript and protein in DOECs was compared to that in the human cultured keratinocyte cell line (HaCaT) cells. Results. EGF protein expression was detected in DOEC cell lysates by both dot blot and ELISA. Strong cytoplasmic EGF immunoreactivity was observed in DOECs, although some cells showed only a weak immunoreactive signal for EGF. Moreover, DOECs, besides containing EGF protein, also expressed transcript for EGF. Interestingly, ELISA analysis revealed that EGF protein contents were higher in DOECs than in HaCaT cells. ELISA analysis also disclosed that EGF concentration was about 10 times higher in whole saliva compared to DOECs. EGF transcript expression was about 50% lower in HaCaT cells stimulated with high (10%) compared to low (0.1%) concentration of fetal bovine serum, representing growth-stimulated and growth-restricted conditions, respectively, implying that growth-stimulus exerts negative feedback on EGF gene activity in HaCaT cells. Conclusion. Here, we show for the first time that DOECs express the EGF, arguing that these cells contribute to salivary EGF contents and hence may play a role in gingival epithelial repair and wound healing.